Effective Preparation of Nanoscale CH3NH3PbI3 Perovskite Photosensitizers for Mesoporous TiO2‐Based Solar Cells by Successive Precursor Layer Adsorption and Reaction Process. Issue 4 (1st December 2019) - Kim, Myoung; Lee, Seul-Yi; Yoo, So-Min; Paek, Sanghyun; Lee, Yonghui; Cho, Kyung Taek; Zimmermann, Iwan; Kim, Hae-Yeon; Kim, Beom-Seok; Song, Min-Kyeong; Shin, Taeho; Kim, Kyoungsoo; et al.
Abstract : Nanoscale CH3 NH3 PbI3 perovskite sensitizers are grown by delivering each precursor successively onto the surface of mesoporous (meso) TiO2 electrodes. Using Pb(NO3 )2 ions as a lead(II) source and CH3 NH3 I (MAI) for methylammonium and iodide sources, repetitive cycles of the two dipping steps are successful in growing few nanometer‐sized MAPbI3 gradually on the TiO2 surface inside the meso‐TiO2 film. However, some aggregates are observed on the top surface of the meso‐TiO2 film due to slight dissolution of PbI2 and its accumulation/reaction with MAI at the top surface of the meso‐TiO2 film. To solve this inhomogeneity of the deposition, a nondestructive multiple deposition route for nanoscale MAPbI3 is suggested as a successive precursor layer adsorption and reaction (SPLAR) process where, from the second cycle of deposition, PbI2 is delivered with the help of an ionic liquid compound dissolved in dichloromethane. With this new Pb precursor in less‐polar solvents, nanoscale MAPbI3 sensitizers are grown without dissolution of preformed perovskites or formation of some aggregates at the top surface. After the third cycle of SPLAR deposition, about 7.0 nm–sized MAPbI3 sensitizers are prepared and display enhanced photovoltaic performance (7.18 ± 0.31%) compared with devices obtained from only one cycle (5.74 ± 0.30%). Abstract : New successive precursor layer adsorption and reaction (SPLAR) is successfully applied to grow nanoscale MAPbI3 perovskite photosensitizers by way of step by step on the surface of mesoporous TiO2 film homogeneously, whereas old successive ionic layer adsorption and reaction (SILAR) is turned out to produce both nanoscale dots inside the film and bigger aggregates at the top surface.